IS ULYSSES REALLY HARD TO UNDERSTAND? - Gao, Meng (International Journal of Research -GRANTHAALAYAH, 2017)
As a representative work of modern stream consciousness novel written by James Joyce in twentieth century, Ulysses differs the traditional novel from the aspects such as the creature source of figure and plot, narration structure, a great number of metaphors and allusions usage and translation version. Therefore, its audiences are almost specialists and scholars who are dedicated to the study of Ulysses and few readers could accept it. The essay will review the novel from the stand of ordinary reader from the perspective of reader response theory to analyze the reason for which it becomes a great challenge for readers all over the world so that there could be some available ways for reader to understand the creation origin of the novel and to interpret it better. Finally, the essay hope that the value of the novel could be propagated and its novel creation could be accepted.